Fiber cables in leaf blades of Typha domingensis and their absence in Typha elephantina: a diagnostic character for phylogenetic affinity. Issue 2 (2nd April 2016) - Witztum, Allan; Wayne, Randy
Abstract : Vertical fiber cables anchored in horizontal diaphragms traverse the air-filled lacunae of the tall, upright, spiraling leaf blades of Typha domingensis, T. angustifolia, T. latifolia and T . × glauca . The fiber cables may make a mechanical contribution to leaf blade stiffness while allowing flexibility under windy conditions. We examined the very tall, upright, spiraling leaf blades of T. elephantina, which can be over 4 m long, for fiber cables. In the tall species of Typha, there are two alternative architectures for upright leaf blades. T. domingensis utilizes fiber cables to enhance stiffness in the tall, upright concavo-convex leaf blades, whereas T. elephantina may maintain their tall stature in the absence of fiber cables by having a different cross-sectional geometry. These alternative architectures can be used as a diagnostic character along with other morphological characters to assess phylogenetic affinity in Typha . The very tall T. elephantina which lacks fiber cables may be more closely related to the much shorter T. minima, which also has no cables, than to the tall T. domingensis and T. angustifolia, both of which have prominent fiber cables . T. elephantina and T. minima share other morphological characters as well.